Modelling of concepts "purpose", "goal", "task", and "function" in law - Čyras, Vytautas (Lietuvos matematikos rinkinys, 2004)
The formalisation of concepts a ``purpose’’, ` ` goal’’, ` ` task’’, and ``` ` function’’ in law is examined. Conceptual graphs called `` ` goal-task graphs’’ are proposed to model them. A goal is associated with a predicate, which characterises the goal. A node represents a state, in which the predicate is true. An edge represents the task. A task e = (u, v) represents a mean to implement the state v, which assumes u.